Isavuconazole shortens the QTc interval - Mellinghoff, Sibylle Christiane; Giesen, Nicola (Mycoses, 2018)
Isavuconazole is a novel antifungal drug approved for the treatment of adults with invasive aspergillosis and mucormycosis. While azoles as a class effect are known to prolong QTc interval, clinical trials have shown that isavuconazole administration may cause shortening in a dose-related manner. Here, we assessed the effects of isavuconazole on the length of QTc interval. The objective of the study was to describe changes in the QTc interval induced by isavuconazole treatment. A total of 26 adult patients from 7 hospitals were included. Patients received isavuconazole for the treatment of invasive fungal infection and, in 1 case, for prophylaxis due to QTc prolongation under fluconazole. Twelve-channel electrocardiograms (ECGs) were performed before and during treatment. Out of 26 patients, 24 showed shortening of QTc interval. In patients with QTc shortening, QTc during isavuconazole treatment showed a mean decrease of 7.4 ± 5.8% (36.5 ± 38.8 ms, range 7-202; P = .004), compared to pre-isavuconazole ECG. One patient with available long-term follow-up showed further decrease in QTc on days 55 and 110. Apart from 1 case report, these are the first data outside controlled clinical trials showing QTc shortening. Knowledge about cardiac effects of isavuconazole will serve to better manage the use of concomitant medications.
First published: 25 November 2017
Gesehen am 25.09.2018